The Impact of the Trans-Sumatran Highway Development on Logistic Cost Efficiency - Dwitasari, Reslyana; Perdana, Yandra Rahadian; Gusleni, Yessi; Meyrawati, Zusnita (IPTEK Journal of Proceedings Series, 2020)
The development of transport infrastructures of the Trans-Sumatran Highway is the policy of the Indonesian government to boost the economic growth. However, on the other hand, this idea needs to be proven since Indonesia has unique regional characteristics in terms of natural, social, and cultural conditions that bring impacts on congestion, low levels of travel security, and illegal costs or surcharges. This problem triggers inefficient logistics activities which can be seen from the high costs of shipping, transportation, and administrative. Therefore, this paper aims to examine the impact of the Trans-Sumatran Highway construction on logistics cost. The result of this study indicates that there are several benefits obtained from the toll road development. For the manufacturers, they may get a faster shipping process so that inventory turnover is getting higher. High inventory turnover can make inventory costs lower. While for the transporters, faster travel times and smooth toll road conditions can reduce the costs of vehicle maintenance and fuel. In addition, the toll road is able to eliminate the surcharges that previously often arise on trips between Lampung and Palembang. This paper argues that the Trans-Sumatra Highway can enhance the transportation and logistics activities.